Evaluation of 3-hydroxypropionate biosynthesis in vitro by partial introduction of the 3-hydroxypropionate/4-hydroxybutyrate cycle from Metallosphaera sedula. (1st September 2016) - Ye, Ziling; Li, Xiaowei; Cheng, Yongbo; Liu, Zhijie; Tan, Gaoyi; Zhu, Fayin; Fu, Shuai; Deng, Zixin; Liu, Tiangang
Abstract: The chemical 3-hydroxypropionate (3HP) is an important starting reagent for the commercial synthesis of specialty chemicals. In this study, a part of the 3-hydroxypropionate/4-hydroxybutyrate cycle from Metallosphaera sedula was utilized for 3HP production. To study the basic biochemistry of this pathway, an in vitro-reconstituted system was established using acetyl-CoA as the substrate for the kinetic analysis of this system. The results indicated that 3HP formation was sensitive to acetyl-CoA carboxylase and malonyl-CoA reductase, but not malonate semialdehyde reductase. Also, the competition between 3HP formation and fatty acid production was analyzed both in vitro and in vivo. This study has highlighted how metabolic flux is controlled by different catalytic components. We believe that this reconstituted system would be valuable for understanding 3HP biosynthesis pathway and for future engineering studies to enhance 3HP production.